Perception of the International Community on the Political Change of 1960 and Referendum of 1980 - Thapa, Binod (NPRC Journal of Multidisciplinary Research, 2026)
Background: King Mahendra’s dissolution of Nepal’s parliamentary system on December 15, 1960, elicited divergent international reactions. Responses to the 1960 Dissolution: India strongly opposed the move, with Prime Minister Nehru expressing concern and socialist leaders staging protests. China remained silent, appearing satisfied with the King’s action. Britain’s Labour Party condemned the proclamation and urged restoration of democracy, though the government maintained stability and allowed Queen Elizabeth’s visit. The United States, wary of communist influence, refrained from criticism, treating the change as Nepal’s internal matter while maintaining diplomatic ties. Overall, responses reflected geopolitical interests, with democratic nations cautious yet prioritizing stability and strategic relations over open opposition. Responses to the 1980 Referendum: The 1980 referendum in Nepal, initiated by King Birendra, offered citizens a choice between a multi-party system and a reformed Panchayat system, with the latter securing majority support. The international community, particularly the United States, viewed the referendum positively as a democratic exercise that broadened participation and reinforced national unity. U.S. officials emphasized Nepal’s right to self-determination and praised the peaceful conduct of the vote. Other nations, such as Austria, also commended the referendum as a stabilizing measure. Conclusion: Global reactions affirmed Nepal’s independence and political legitimacy.